Further Evidence for Ground Dominance in Control Of Speed During Low Altitude Flight. (September 2013) - Meyer, Mark; Adamic, Eric J.; Dyre, Brian P.
Previous research found that during simulated low-altitude flight, optical control of speed is based on the flow rate projected by the ground, even when changes in altitude make this information unreliable and other sources of speed information, such as the flow rate of a cloud layer above the flight path, could provide more valid information. However, in these studies factors such as color and contrast differences between the ground and clouds may have contributed to ground dominance. Further, it is possible that ground dominance results from an inability to integrate flow distributed across different surfaces in the environment. Here we report two experiments that test whether these factors contribute to ground dominance. We found ground dominance to be independent of color and contrast differences between the ground and cloud surfaces and that control of speed is based on global optical flow defined across multiple surfaces when these surfaces do not represent the ground.